How We Learn Together: Young Children (and Their Mums) Using Animal Metaphors and Imagery to Understand and Manage Learning - Jelfs, Helen (LEARNing Landscapes, 2013)
In this paper I discuss the "Language for Learning" project which used animal metaphors and imagery in an early childhood education setting as a way of enabling children to understand and manage their own learning. The concept of "learning power" was communicated through metaphor and the use of image, movement, and music, which in turn led to the development of a rich and local language for learning. An unexpected outcome of this project was its capacity to generate positive learning experiences for young children and their parents, and to generate personal and social transformation within the wider community.